User Feedback at Scale: Spotlight on UX Research for Enterprise Systems. (September 2016) - Smith, Danielle; Fadden, Steve; Meingast, Melissa; Peterson, Michelle; Rowe, Anna
A strong User Experience (UX) discipline has become a business imperative across commercial industry. Accordingly, Human Factors professionals may be part of UX teams in large organizations designing enterprise systems (business-to-business technologies that serve as corporate back-ends or enabling technologies for other products). These teams integrate user research into their design processes by using methods that are similar to consumer product researchers, but often differ in terms of scope and timeline. This panel aims to share best practices and lessons learned in business-to-business UX by bringing together leaders from different enterprise technology companies. Panelists will discuss (1) logistics of gathering feedback from a limited, sometimes hard to reach group of users, (2) how to gather technical feedback using (sometimes) non-technical researchers, and (3) how to structure a user research team (and their deliverables) to effectively turn that feedback into business direction and product experience feedback within an enterprise technology company.